PENGARUH MOTIVASI KARIR , MOTIVASI SOSIAL, MOTIVASI PENGETAHUAN DAN MOTIVASI EKONOMI TERHADAP MINAT MAHASISWA DALAM MENGIKUTI PROGRAM BREVET PAJAK - Agung, Qoyum Muhammad; Astriani, Devi; Nasihin, Ihsan (Peneliti.net, 2024)
This study aims to determine the interest of Buana Perjuangan University students in participating in the tax brevet program, this type of research is quantitative and is analyzed using the multiple linear regression method with sampling using the Random Sampling method from Buana Perjuangan University Accounting students who are taking or have taken Tax courses . The four variables studied are Career Motivation, Social Motivation, Knowledge Motivation and Economic Motivation and Student Interest in Joining the Tax Brevet Program. by using a questionnaire then carried out validity test, reliability test, classic assumption test, model accuracy test and hypothesis test to find out the research results. With the research method that has been done, the results show that career motivation, knowledge motivation have a significant effect, while social motivation and economic motivation have no effect on students' interest in participating in the tax brevet program.